Multi-objective supplier selection and order allocation under disruption risk. (November 2016) - PrasannaVenkatesan, S.; Goh, M.
Highlights: A multi objective model is formulated for sourcing under supply disruption risk. A hybrid fuzzy AHP, fuzzy PROMETHEE and a Multi objective PSO is used as solution methodology. From the results, the preferred suppliers are underutilized to minimize the expected loss due to disruptions. The effect of mis-estimating the supplier failure probability on expected total cost is less when more suppliers are chosen. The expected total cost is less sensitive to the variation in the output flexibility when multiple suppliers are selected. Abstract: We formulate a multi-objective MILP model to find the optimal choice of suppliers and their order quantity allocation under disruption risk. Suppliers are evaluated and ranked, based on the preference values obtained using a hybrid fuzzy AHP-fuzzy PROMETHEE. Multi-objective Particle Swarm Optimization is then applied to yield a set of Pareto-optimal solutions for the choice of suppliers and their order allocation. Numerical experimentation suggests that the supplier failure probability affects the expected total cost more than supplier flexibility and loss cost. Sensitivity analysis is performed on the failure probability, the output flexibility, and loss cost of the suppliers.